SI TUTI-BASED GIRLS' SCHOOL (ANTI-STUNTING LITERACY) - Nurmalasari, Intan Rohma; Rosyidah, Rafhani; Taufiq, Wahyu (Antis-publisher, 2024)
Background: Stunting is a major public health issue in Indonesia, particularly in rural areas where limited access to health information exacerbates the problem. Empowering women through health literacy is essential in addressing stunting and related health risks. Specific Background: In Gedangan Village, Pasuruan Regency, high rates of stunting, poor maternal nutrition, and the prevalence of early marriage have been identified as key challenges. Existing interventions have lacked comprehensive, community-based approaches to stunting prevention. Knowledge Gap: There is a need for scalable models that combine education, digital tools, and community involvement to effectively address stunting at the local level. Aims: This study aimed to evaluate the impact of the SI TUTI (Anti-Stunting Literacy) Based Women's School Program, designed to empower women through education and digital resources to reduce stunting rates. Results: The program involved PKK Cadres, Posyandu, and Aisyiyah Branch Members, with the SI TUTI mini book and ASTUTI application as key tools. Post-training assessments showed a 30% increase in participants' understanding of stunting, with a 95% satisfaction rate regarding educational materials and media. The use of digital tools facilitated improved access to health information. Novelty: This program integrates traditional education methods with digital innovations, offering a replicable model that addresses stunting at the grassroots level, enhancing community engagement through localized content and accessible health literacy tools. Implications: The program demonstrates potential for broader application in similar rural contexts, contributing to the achievement of the 2030 Sustainable Development Goals related to public health and well-being. Future efforts will focus on program expansion and continuous evaluation to ensure long-term sustainability and effectiveness in stunting prevention.